Spray vaccination with an improved F Newcastle disease vaccine. A comparison of efficacy with the B1 and La Sota vaccines - Ibrahim, Abdul Latiff; Lai, M. C.; Ideris, Aini (Elsevier, 1983)
An improvied F Newcastlc disease vaccine was evaluated as a spray vaccine, Its performance was compared with the B I and La Sota vaccines, two other commercial lentogenic Newcastle disease vaccines. The three different vaccines when administered by spray to groups of chitkens at 2 I and 42 days old stimulated satisfactory haemagglutination inhibition (HI) antibody response up to nine weeks. Chickens vaccinated with any of the three vaccines were protected against the virulent Newcastle disease virus. It was concluded that there was no significant difference between the improved F Newcastle disease vaccine and the two commertial vaccines in immunizing capacity, protection and stress effects,